Variation in coexisting birds to exploit spatial heterogeneity in small mammal activity. (13th December 2018) - Emmering, Quinn C.; Kelly, J. K.; Ostfeld, R. S.; Schmidt, K. A.
Abstract : Breeding nest site selection is often the first defense against nest predation risk. To be effective, this mechanism requires site‐specific spatial heterogeneity in predator abundance which produces predator‐poor space, prey's ability to assess spatial heterogeneity in risk, and few or weak constraints on the ability to settle in within predator‐poor space. We used a 15‐yr dataset on forested grids that provided extensive records of fledging success of veeries Catharus fuscescens and ovenbirds Seiurus aurocapilla in relation to areas of low and high spatial clustering of an important nest predator, the eastern chipmunk Tamias striatus . Ovenbird nests were built in locations with significantly lower chipmunk clustering at a scale of 900 m 2, relative to random locations within our study grids. In contrast, veery nests were built at sites with significantly higher chipmunk clustering relative to random locations. Veery nest site preference for dense shrub patches may increase their vulnerability to chipmunks seeking shrubs to reduce their own vulnerability to predators. Despite interspecific differences in nest placement and avoidance of chipmunk clusters, for both species fledging success was unaffected by surrounding chipmunk activity. This study highlights key differences in the use of predator‐poor space among coexisting species, and highlights the need to consider constraints due to other habitat preferences and large predator communities.